STUDI TENTANG CITRA RAGA DAN PENYESUAIAN SOSIAL TERHADAP TEMAN LAKI-LAKI PADA SISWI SMA PEDESAAN DAN PERKOTAAN - Untari, Sri (Universitas Sahid Surakarta, 2012)
This research aims to understand the correlations between body image with social adjustment for male friends in rural and urban high school students, especially for the social adjustment differences. The research sample was 100 students in 2ndgrade SMUN 9 DIY, majority lived in the city, and 2ndÂ grade from SMUN Ngemplak, majority lived in rural. Random sampling technique was used and questionnaire as a collecting data methods was used.Â Analysis method using product moment correlations. The following conclusions are body image does give a positive correlation and significantly with social adjustment of male friends, the body image give 37,67% effective contribution to social adjustment. It shows that social adjustment of male friends in urban highschool get higher score than rural high school.